The κ-Opioid Receptor Agonist U50488H Ameliorates Neuropathic Pain Through the Ca2+/CaMKII/CREB Pathway in Rats - Zhang XM; Lun MH; Du W; Ma F; Huang ZQ (Dove Medical Press, 2022)
Xiao-Min Zhang, Ming-Hui Lun, Wei Du, Fang Ma, Ze-Qing Huang Department of Anesthesiology, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institution, NO.44 Xiaoheyan Road, Dadong District, Shenyang, Liaoning Province, 110042, People's Republic of ChinaCorrespondence: Xiao-Min Zhang; Ze-Qing Huang Department of Anesthesiology, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institution, No.44 Xiaoheyan Road, Dadong District, Shenyang, Liaoning Province, 110042, People's Republic of China Email zhangxiaomin.99@163.com; huangzeqing0@163.comObjective: To observe the ameliorative effect of kappa opioid receptor (KOR) agonist on rats with neuropathic pain (NP) and investigate the mechanism of action of the calcium ion (Ca2+)/calcium/calmodulin-dependent protein kinase II (CaMKII)/cyclic AMP response element-binding protein (CREB) pathway.Methods: A total of 40 Sprague Dawley rats were randomly divided into four groups: sham-operation group (Sham group), NP model group (NP group), NP + KOR agonist U50488H group (NU group) and NP + specific CaMKII antagonist (KN93) + U50488H group (NKU group). The thermal withdrawal latency (TWL) and mechanical withdrawal threshold (MWT) of each group of rats were determined. ELISA was applied to examine the changes in inflammatory factors and oxidative stress factors, and the apoptotic rate in dorsal root ganglia was observed using TUNEL staining. Ca2+ concentration, content of oxidative stress index ROS and the release of calcitonin gene-related peptide (CGRP) and N-methyl-D-aspartate receptor (NMDAR) in the dorsal root ganglia were measured by the immunofluorescence assay. Finally, Western blotting was performed to detect expression changes in the Ca2+/CaMKII/CREB pathway.Results: The KOR agonist U50488H could improve the values of TWL and MWT of NP the rats, inhibit inflammatory responses and relieve oxidative stress injury. Its mechanisms of action were associated with U50488H repression of Ca2+ influx, reduction of CGRP and NMDAR releases in the dorsal root ganglia and decreases in CaMKII and CREB phosphorylations in NP rats.Conclusion: The KOR agonist ameliorates NP through suppressing the activity of the Ca2+/CaMKII/CREB pathway.Keywords: KORs, neuropathic pain, Ca2+, CaMKII, CREB